Concept of Decision in Absentia and its Adjudication Principles - Pridon Basilia (European Scientific Journal, ESJ, 2017)
Decision in absentia is the decision passed against an absent party. Such decision is based on the supposition that at the main judicial sitting the plaintiff denied the suit, and the defendant has notified it. Every person has the right to go to law in order to defend his rights or liberty. According to the 1st part of the 2nd paragraph of the Civil Procedure Code, the juridical protection is enforceable for every person. The court will start trying a case with the application of that person who applies for it in order to defend the interests, legally provided. The main point of this principle should be divided into two parts and explained. Hence, in the first case, the plaintiff is pondered who has a demand towards the defendant; he thinks that the defendant has outraged the rights and the interests protected by law and he wants these rights to be urgently rehabilitated. For this he has saved some money, time, and work, to be present at the legal trial and to give the judge the chance to rehabilitate his rights. On the stage of preliminary preparation of the case the argument is not solved essentially. Only the procedural actions, foreseen by the law are held. On the preparatory stage may be held preparation session, but in this case, the supposition of suit confession by the defendant, or the sides’ agreement, defendant denial of suit may not be justified. That is why, in case of absence of any side at the main trial, as the argument decision has turned to be impossible; it is not possible to pass the absent decision. The absent decision is the presumption for the side, which has lost the case with substantive point of view because of being absent. A decision in absentia is a supposition that the plaintiff refuses the suit in case he is absent, or the defendant has confessed the action, while his absence. As this supposition was not justified at the preparation trial, it is not possible to pass the decision at this stage and the essential discussion of the case should be set at the main trial.